Auditor quality and the role of accounting information in explaining UK stock returns - Mark A. Clatworthy; Christopher K .M. Pong; Woon K. Wong (Cardiff University, Cardiff Business School, 2009)
Using a variance decomposition approach, we examine the importance of accounting information - in particular the cash flow and accruals components of earnings - in explaining the variation in UK company stock returns. We extend prior research by analysing whether auditor quality moderates the role of accruals and cash flows in driving returns on both a relative and an absolute basis. Moreover, we employ a new orthogonal variance decomposition which reduces the influence of the covariance terms on the variance decomposition results. In general, our results indicate that both components of earnings are important drivers of stock returns and suggest that the significance of both earnings components varies conditional on auditor quality. Although there are some similarities with US-based research, a number of differences are also evident. In particular, cash flow news seems more important in the UK than in the US.
Keywords: 330; Aktienmarkt; Börsenkurs; Wirtschaftsprüfung; Informationswert; Dienstleistungsqualität; Großbritannien